2012
DOI: 10.1016/j.eats.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Repair of Chronic Bony Bankart Lesion Using a Low Anterior Portal

Abstract: Abstract:We describe the repair of a chronic bony Bankart lesion in a case with recurrent instability using standard techniques and equipment for addressing anteroinferior glenohumeral instability. A 25-year-old man with recurrent instability and a chronic bony Bankart lesion with a Hill-Sachs lesion was treated. The inferior 2 sutures and knotless anchors are placed through a low anterior portal, which improves the angle of approach to the inferior portion of the glenoid that is fractured. The knotless anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Since then, numerous arthroscopic techniques to address Bankart fractures have been published. [5][6][7][8][9][10][11][12][13][14] Despite the high incidence (4% to 70%) of bony Bankart lesions after shoulder dislocation, few clinical outcome studies of arthroscopic bony Bankart repair have been published to date. [1][2][3]11,[15][16][17] Most of the published clinical trials focus on the size of the remaining defect, as shown by computed tomography (CT), as well as the influence of fragment reduction and bony healing on postoperative failure and patient satisfaction.…”
mentioning
confidence: 97%
“…Since then, numerous arthroscopic techniques to address Bankart fractures have been published. [5][6][7][8][9][10][11][12][13][14] Despite the high incidence (4% to 70%) of bony Bankart lesions after shoulder dislocation, few clinical outcome studies of arthroscopic bony Bankart repair have been published to date. [1][2][3]11,[15][16][17] Most of the published clinical trials focus on the size of the remaining defect, as shown by computed tomography (CT), as well as the influence of fragment reduction and bony healing on postoperative failure and patient satisfaction.…”
mentioning
confidence: 97%